[Rezension von: The shape of stories : narrative structures in cuneiform literature] - Tadmor, Eli (JAOS, 2025)
The Shape of Stories: Narrative Structures in Cuneiform Literature. Edited by Sophus Helle and Gina Konstantopolos. Cuneiform Monographs, vol. 54. Brill, 2023. Pp. xi + 354. $155.